Contrasting nidification behaviors facilitate diversification and colonization of the Music frogs under a changing paleoclimate - Zhi-Tong Lyu; Zhao-Chi Zeng; Han Wan; Qin Li; Atsushi Tominaga; Kanto Nishikawa; Masafumi Matsui; Shi-Ze Li; Zhong-Wen Jiang; Yang Liu; Ying-Yong Wang (Communications Biology, 2024)
Abstract In order to cope with the complexity and variability of the terrestrial environment, amphibians have developed a wide range of reproductive and parental behaviors. Nest building occurs in some anuran species as parental care. Species of the Music frog genus Nidirana are known for their unique courtship behavior and mud nesting in several congeners. However, the evolution of these frogs and their nidification behavior has yet to be studied. With phylogenomic and phylogeographic analyses based on a wide sampling of the genus, we find that Nidirana originated from central-southwestern China and the nidification behavior initially evolved at ca 19.3 Ma but subsequently lost in several descendants. Further population genomic analyses suggest that the nidification species have an older diversification and colonization history, while N. adenopleura complex congeners that do not exhibit nidification behavior have experienced a recent rapid radiation. The presence and loss of the nidification behavior in the Music frogs may be associated with paleoclimatic factors such as temperature and precipitation. This study highlights the nidification behavior as a key evolutionary innovation that has contributed to the diversification of an amphibian group under past climate changes.